Digital Literacy as a Fundamental Competency in the 21st Century Education - Zaid Budi Arifin; Farkhan, Muhammad Nur; Tasjuddin, Muhamad Roshif; Rahmadhani, Syaiful Aziz; Salsabila, Unik Hanifah (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: This research aims to explore the role of digital literacy in improving the quality of learning in the 21st century through several main aspects, namely digital literacy in the context of education, in the learning process the role of teachers in supporting digital literacy and the application of digital literacy in education. Digital literacy plays an important role to help students and educators utilize technology effectively in the learning process. However, this ease of access does not always mean that the information obtained can be used immediately without in-depth understanding. Purpose: The main purpose of this study is to develop a deeper understanding of the importance of digital literacy in education and provide a clearer direction in implementing digital literacy in educational institutions in Indonesia. Design/methods/approach: This research uses descriptive qualitative research through a library study approach. The method of collecting sources in this research uses literature review on books and scientific articles published online and research related to the types of research in quantitative and qualitative research. The data is related to the role of digital literacy in improving the quality of learning in the 21st century. Findings: This study concludes that digital literacy in developing quality learning in the 21st century confirms the importance of digital literacy skills as a fundamental aspect of modern education. Digital literacy gives students and teachers the ability to adapt to rapid technological change, allowing for more interactive, collaborative and contextualized learning experiences.